Effect of the morphology of solution‐grown ZnO nanostructures on gas‐sensing properties. Issue 12 (7th August 2017) - Zhang, Shaolin; Nguyen, Son T.; Nguyen, Thuy H.; Yang, Woochul; Noh, Jin‐Seo
Abstract: Despite the great potential of zinc oxide (ZnO) nanostructures as a sensing material for high‐performance gas sensors, the correlation between the morphology of ZnO nanostructure and its gas‐sensing performance has not been systematically investigated yet. In this work, ZnO nanostructures with controlled morphologies were synthesized by low‐temperature solution route and chemical bath deposition method. Thin film gas sensors were fabricated from the nanostructures and the sensor performance such as the response, recovery time, and stability was examined for several gases. It is demonstrated that the gas‐sensing performance of a ZnO nanostructure sensor is strongly influenced by its morphology. One dimensional ZnO nanocones are highly promising for practical application to gas sensors, due to their large surface area per unit mass and unique conical structure.